An Inquiry into the Use and Usefulness of Performance Dashboards in Construction Enterprises across West Region of Romania - Marius PANTEA; Andrei PELIN (Revista de Management Comparat International)
The amount of information required to be processed by a manager daily, disregarding his or her hierarchic level, tend to get excessive as the information systems become more complex and wider spread across the processes and activities performed within an organization. One of the solutions offered by theoreticians and accepted in practice is the performance dashboard – a synthetic and efficiently comprised set of economic and financial indicators through which a decision maker is informed about the state and evolution of organizational components he or she is responsible for. As long theory is abundant in different models of performance dashboards, recommendations regarding its structure, methods to use dashboards in decisional processes, in the business world there is no type of dashboard to be considered as a generally accepted one, some managers being unaware that they use such a decision making instrument. The aim of this paper is to establish, through analysis of responses to a questionnaire, whether managers of constructions enterprises from the West Region of Romania use dashboard, what information content deliver their dashboards and to what extend it comprises a useful decision making tool.